Gestures in EFL classroom: Their relations with complexity, accuracy, and fluency in EFL teachers' L2 utterances. (April 2020) - Sato, Rintaro
Abstract: This observational study was conducted to examine the effects of Japanese English as a foreign language (EFL) teachers' gestures on their second language (L2) utterances in EFL lessons. Two English lessons, one in a public senior high school and another in a private junior high school, taught by Japanese EFL teachers were video and audio recorded, transcribed, and analyzed. The teachers' L2 utterances were analyzed in terms of complexity, accuracy, and fluency to examine the following: (1) whether there is a difference between L2 utterances with and without gestures and (2) whether there is a difference in the effect of gestures according to their types. The results were as follows: (1) L2 utterances are more complex and fluent with gestures but accuracy was equal when accompanied by gestures and (2) there is a difference in the relations of some specific types of gestures to L2 utterances, with metaphoric gestures showing the highest scores in complexity and fluency and emblems the lowest. These findings suggest that teachers' gestures play a crucial role in EFL classrooms, and therefore, should be given more consideration in L2 teacher education and training programs.